2020
DOI: 10.3847/1538-4357/ab99a5
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Peculiar A and F Stars with Enhanced s-process and Iron-peak Elements: Stellar Radiative Acceleration at Work

Abstract: We present 15,000 metal-rich ([Fe/H]>−0.2 dex) A and F stars whose surface abundances deviate strongly from solar abundance ratios and cannot plausibly reflect their birth material composition. These stars are identified by their high [Ba/Fe] abundance ratios ([Ba/Fe]>1.0 dex) in the LAMOST DR5 spectra analyzed by Xiang et al. They are almost exclusively main-sequence and subgiant stars with T eff 6300 K. Their distribution in the Kiel diagram (T effg log ) traces a sharp border at low temperatures alo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 110 publications
(160 reference statements)
1
22
0
Order By: Relevance
“…Importantly, for most of the elements, the dispersion in abundances among the seven Li-rich stars is in good agreement with (and, for some elements, lower than) the spread in initial abundances depicted by G-type stars. The only elements for which the seven stars deviate from the bulk are Ca, Cu, and Ba, with one star also showing a slight underabundance in C. The Ba overabundances observed in five of the seven stars are, however, lower than the minimum value assumed by Xiang et al (2020) to characterise metal-rich AmFm stars; additionally, for this element, NLTE effects could potentially be important (Mashonkina et al 2020) and may blur the comparison with the abundances derived for cool stars. This analysis thus tends to indicate that the seven Li rich stars in GALAH bin 4 have relatively normal abundances of heavy elements.…”
Section: Toward a Reliable Conclusion On The LI Trend In The High Metallicity Regimementioning
confidence: 77%
“…Importantly, for most of the elements, the dispersion in abundances among the seven Li-rich stars is in good agreement with (and, for some elements, lower than) the spread in initial abundances depicted by G-type stars. The only elements for which the seven stars deviate from the bulk are Ca, Cu, and Ba, with one star also showing a slight underabundance in C. The Ba overabundances observed in five of the seven stars are, however, lower than the minimum value assumed by Xiang et al (2020) to characterise metal-rich AmFm stars; additionally, for this element, NLTE effects could potentially be important (Mashonkina et al 2020) and may blur the comparison with the abundances derived for cool stars. This analysis thus tends to indicate that the seven Li rich stars in GALAH bin 4 have relatively normal abundances of heavy elements.…”
Section: Toward a Reliable Conclusion On The LI Trend In The High Metallicity Regimementioning
confidence: 77%
“…We note that such stars are prevalence in the hot stars regime; it is suggested that a high fraction of A stars could be chemically peculiar (e.g. Gray et al 2016;Qin et al 2019;Xiang et al 2020), and this is why their high number density constitutes a prominent stripe in the T eff −log g plane. Such artefact reveals one of the limitations of the current model, which tends to yield incorrect log g for these chemically peculiar stars.…”
Section: T Eff and Log Gmentioning
confidence: 79%
“…17 shows that at the cool temperature side (T eff 10000 K), there is a large fraction of stars with super-solar metallicity, forming the high-[Fe/H] tail of the [Fe/H] distribution. Many of these super-solar metallicity stars are probably AmFm stars, which have been demonstrated to contributed a large fraction (∼ 40%) of the A/F stars with mass higher than 1.4M in the LAMOST sample (Xiang et al 2020).…”
Section: Abundance [Fe/h] and [Si/h]mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the LAMOST [Fe/H] estimates can be rebost down to −2.5 dex (see Fig. 10 of Conroy et al 2019); DD-Payne can also generate reasonable [Ba/Fe] stars with 1 < [Ba/Fe] < 3 dex and 𝑇 eff > 7000K (Xiang et al 2020).…”
Section: Performance Of Muse Stellar Label Extraction Under Different...mentioning
confidence: 99%